Digital Marketing Investment and The Sustainability Performance of Manufacturing Firms in Emerging Markets - Akuma, John Kwame; Akude, Derrick Nukunu; Kwaning, Emmanuel Addai; Amoah-Ahinful, Isaac Kwame (International Journal of Accounting and Economics Studies, 2025)
This paper investigated the relationship between digital marketing investment and the sustainability performance of manufacturing firms in ‎emerging markets. The survey utilized a self-administered questionnaire approach, gathering a total of 287 completed responses for data ‎analysis utilizing Smart PLS-SEM (version 4). The study reveals that digital marketing capability has a significantly positive effect on environmental performance. Similarly, digital marketing capability has a significant impact on financial performance. However, ‎digital marketing capability exhibits no statistically significant effect on social performance. Furthermore, digital marketing strategic integration exhibits a significant effect on both environmental and social performance. Also, digital marketing strategic integration has a ‎statistically significant, but negative effect on financial performance. The adoption of digital marketing technologies demonstrates a positive‎ly significant influence on financial performance. Also, the adoption of digital marketing technologies positively affects social performance ‎significantly. Moreover, the adoption of digital marketing technologies has a significant effect on environmental performance. ‎This investigation provides insights into the value of digital marketing investment and the sustainability performance of manufacturing firms ‎in emerging markets, thereby highlighting their implications for theory, managers, and business success‎.